Implementation behavior of communities regarding relatives caring for people with dementia: original contributions - Wittek, Maren; Manke-Reimers, Fabian; Schmitt, Eric (Zeitschrift für Gerontologie und Geriatrie, 2024)
Actors from the community (CAs) play a fundamental role in the support of caring relatives (CRs) of people with dementia (PWD). As their support is not sufficient, the implementation of support services needs to be optimized; however, little is known about the factors associated with the implementation behavior of CAs.